The different faces of inclusion and exclusion - Mascareño, Aldo (2015)
The notions of inclusion and exclusion have a long tradition in sociology, but have gained significant currency more recently in public policy analysis. However, a certain conceptual inflexibility arises when the distinction is applied to complex social situations. This article examines the main approaches to inclusion/exclusion in the sociological tradition, systems theory and the theory of new inequalities. On this basis, five interrelated situations of inclusion and exclusion are constructed: self-inclusion/self-exclusion, inclusion by risk/exclusion by danger, compensatory inclusion, inclusion in exclusion and sub-inclusion. They are illustrated with specific examples to refine an analytical approach to problems of inclusion and exclusion, with a view to contributing to sociological analysis and to assessing the consequences of public and private decisions.